Structure and Excited-State Dynamics of Dimeric Copper(I) Photosensitizers Investigated by Time-Resolved X-Ray and Optical Transient Absorption Spectroscopy - Lemus-Chavez, L; Lemus-Chavez, L; Aravena-Ponce, D; Aravena-Ponce, D; Levín-Vásquez, P; Levín-Vásquez, P; Llanos-Silva, L; Llanos-Silva, L (Royal Society of Chemistry, 2021)
Time-resolved X-ray (tr-XAS) and optical transient absorption (OTA) spectroscopy in the picosecond time scale coupled with Density Functional theory (DFT) and X-ray absorption near-edge structure (XANES) calculations are applied to study three homoleptic Cu(i) dimeric chromophores with ethyl and longer propyl spacers, denoted as [Cu2(mphenet)2]Cl2(C1), [Cu2(mphenet)2](ClO4)2(C2) and [Cu2(mphenpr)2](ClO4)2(C3) (where mphenet = 1,2-bis(9-methyl-1,10-phenanthrolin-2-yl)ethane and mphenpr = 1,3-bis(9-methyl-1,10-phenanthrolin-2-yl)propane). Tr-XAS analysis after light illumination at ∼ 100 ps illustrate the formation of a flattened triplet excited state in all 3 complexes. Optical transient absorption (OTA) analysis forC1monitored in water andC2andC3measured in acetonitrile reveals distinct excited-state lifetimes of 169 ps, 670 ps and 1600 ps respectively. These differences are associated to changes in the solvent (comparingC1andC2) and the flexibility of the ligand to adapt after Cu flattening upon excitation (C2andC3). Our results are important for the improved structural dynamics of these types of Cu-based dimeric compounds, and can guide the integration of these chromophores into more complex solar energy conversion schemes. © the Owner Societies 2021.